Development of environmental laws in India - Kohli, Kanchi; Menon, Manju (Cambridge : Cambridge University Press, 2021)
Development of Environmental Laws in India highlights the dynamic nature of environmental law-making in India between the judiciary, the executive and the parliament. This has led to the creation of a wide range of environmental institutions and bodies with varied roles and responsibilities. The book contains a large volume of materials from the late 1990s, which show a marked shift in the nature of environmental governance in India. These materials offer an understanding of the contemporary debates in environment law in the context of India's economic liberalisation. The materials are thematically organized and presented in an accessible manner. The chapters contain definitions and specific clauses from the legal instruments and refer to court orders and judgements on these themes.
Fundamentals of environmental law -- Institutions regulating India's environment -- Forest reservation and conservation -- Pollution control and prevention -- Environmental protection -- Wildlife and biodiversity conservation -- Ground and surface water extraction -- Land acquisition -- Climate change and policy frameworks -- Contemporary environmental law reforms.
Title from publisher's bibliographic system (viewed on 30 Jul 2021).
Keywords: Environmental law -- India; Environmental policy -- India; Climatic changes -- Law and legislation -- India; Pollution -- Law and legislation -- India; Wildlife conservation -- Law and legislation -- India; Forest conservation -- Law and legislation -- India